1989
DOI: 10.5271/sjweh.1888
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nickel carcinogenesis.

Abstract: Recent investigations on possible mechanisms of nickel carcinogenesis are reviewed, emphasizing cellular uptake and intracellular translocation of nickel, morphological transformat ion of cells by nickel compounds, chromosomal damage, DNA strandbreaks and DNA-protein complexes produced by nickel compounds, mutagenic effects of nickel, influence of nickel on the helical transition of B-DNA to Z-DNA, nickel-inducedinfidelity of DNA synthesis. free radicals and lipid peroxidation induced by nickelexposures, nicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(91 citation statements)
references
References 66 publications
2
88
0
1
Order By: Relevance
“…Nickel (Sunderman 1989) ions have been implicated as chemical reagents that disturb signal transduction. It has been shown that intracellular signaling mediated by calcium ions is involved in the differentiation of oral-aboral ectoderms (Akasaka et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Nickel (Sunderman 1989) ions have been implicated as chemical reagents that disturb signal transduction. It has been shown that intracellular signaling mediated by calcium ions is involved in the differentiation of oral-aboral ectoderms (Akasaka et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequence indicates that Ep45 is a secreted glycoprotein and a member of the serine protease inhibitor (serpin) superfamily. Moreover, Ep45 is a Ni 2ϩ binding protein and is implicated in Ni 2ϩ -induced teratogenesis (25,26). In this report, we performed functional analyses of Ep45 in the interaction between BMP and its antagonist follistatin and found that Ep45 blocked the binding of BMP to follistatin.…”
mentioning
confidence: 85%
“…A model for nickel carcinogenesis can be based on the assessment of the bioavailability of nickel ion at nuclear sites of respiratory target cells (7,(43)(44)(45). This model predicts that it is not just the presence of nickel in a given inhaled substance that determines its carcinogenic potential but rather whether this nickel is bioavailable in sufficient amounts at nuclear sites of epithelial cells to result in respiratory tumor induction.…”
Section: Respiratory Model For Nickel Carcinogenesismentioning
confidence: 99%